Digital transformation for enhancing LSP (Logistic Service Provider) performance - Muhammad Taufani; Anton Wachidin Widjaja (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
Digital transformation has recently become a way to attain competitive advantages and company differentiation. Digital transformation encompasses an organization’s ability to adapt, respond, and position itself for success in the face of rapid technology evolution. However, the implications are of the digitalization of processes for the performance of companies is still unclear as the transition from one process to another is a challenge for everyone involved that impact on firms’ performance. This research endeavors to address the question of how to enhance digital transformation for better performance through exploring the relationships among firms’ adaptability, resource orchestration and innovation capability. This study used questions formulated using indicator that has been developed on previous study, which enables respondents to display a favorable or unfavorable attitude toward the object of interest. This study was conducted using the survey method. Data were collected using questionnaires sent to 70 middle managers and top-level management of logistics service provider companies that are based in Indonesia. Then the structural equation modeling (SEM) path analysis were adopted to test all hypotheses as developed in this study. This study seeks to contribute to a better understanding of digital transformation by analyzing adaptability, resource orchestration and innovation capability that led companies to adopt new digital transformation and their consequences in terms of performance. The overall impact regarding the digital transformation to logistic firms’ performance seems to be moderately positive. The research presented gives an indication of the impact of the adaptability, resource orchestration, and innovation capability being central for Digital Transformation in logistics firms.